Políticas públicas sobre diversidade sexual na educação e vivências pedagógicas de professoras lésbicas na escola : notas sobre a cidade de Vitória - Meireles, Ariane Celestino (2012)
The study investigates the dynamic of debate on sexuality, homophobia and related themes in the public schools of the County of Vitória, based on evidence of statements made by lesbian and bisexual female teachers who teach students belonging to the primary education up to the eighth year. The objective is to determine if the sexual identity of such female teachers is an important element in such context and to investigate which instruments materialize the public policy for sexual diversity in education, at the local level of the County of Vitória public school system, as well as at the national level. The analysis of subjectivities in the construction of the political lesbian and bisexual subject, based on the statements of the respondents who were willing to participate and on the refusal of others, brought evidence of the hiding of non-normative sexuality in order to secure professional respect. Evidence of institutional homophobia brought by the statements indicates that students and teachers, both female and male, are target of discrimination on basis of sexual orientation in the schools. Such evidence reveals the lack of investment by the County in the public policy for sexual diversity in education. The additional analysis of the instruments used at the national level suggest a trend towards promoting sexual education based on a heterosexual perspective, with emphasis on preventing pregnancy and sexually transmitted diseases, but lacking both the debate on gender and sexual equity and any attempt to enhance the social status of lesbians, gays and transsexuals. The study highlights the instruments which deal with sexual diversity, but whose implementation is hindered by institutional homophobia, and proposes actions to promote public policies directed to gender and sexual equity in the public school system of the County of Vitória.